FROM SOCIAL CHARITY TO STRATEGIC INVESTMENT: Reorientation of Waqf Utilization From Maqâsid Al-Shari'ah Perspective in Lhokseumawe - Kafrawi, Kafrawi; Yuslem, Nawir; Tanjung, Dhiauddin; Mardika, Andi (UIN Sumatera Utara, 2025)
This study examines the reorientation of waqf utilization from a traditional social charity approach toward strategic investment from maqâsid al-shari'ah perspective. The transformation of contemporary waqf reflects a shift from charity-oriented practices to an investment-driven model. This research employs a qualitative field method, with data collected through interviews and participatory observation. Data analysis is conducted using As-Syatibi's maqâsid al-shari'ah framework. The findings reveal that the five pillars of maqâsid al-shari'ah provide an effective framework for assessing the productivity and socio-economic impact of waqf utilization. The maqâsid-based approach enables the integration of Islamic spiritual values with community economic empowerment. This study concludes that incorporating maqasid principles into waqf management can optimize the potential of national waqf assets as a driver of sustainable economic development. Therefore, the development of productive waqf models oriented toward strategic investment while maintaining Sharia values is strongly recommended.Keywords: Islamic economics, maqâsid al-shari'ah, productive waqf, strategic investment, sustainable development